Sodobni izzivi in dileme: konferenčni zbornik / 27. posvetovanje Medicina, pravo in družba, 23. - 24. marec 2018, Maribor, Slovenija (University of Maribor Press, 2018)
Contemporary Challenges and Dilemmas : Conference Proceedings / 27th Conference Medicine, Law & Society. The 27th conference Medicine, law and society, with the desire and goal of proceeding, analyzing and discussing open issues, related to medicine and law and the wider society, includes topics dedicated to contemporary challenges and issues, which many domestic and foreign speakers will, together with other participants of the conference, try to find answers.Vaccination is a particularly burning issue in this context, which is associated with recent outbreaks of measles in several European countries, with difficulties in implementing compulsory vaccination in Slovenia and novelties, brought by the ZNB amendment and finally, also with the importance of vaccination at older age and at the workplace. Issues related to the terminal phase of the disease and the patient’s death itself are multifaceted, due to which the approach to this topic will be multidisciplinary, including medical, legal, religious, and ethical aspects. With the goal to ensure a quality healthcare system and health services, the issue of liability is one of the key dilemmas, since it is important to ensure safety, not only for patients but also for doctors. Special importance in this will be given to the so-called “no-fault” system in Slovene legal order and the importance of judicial expertise in judicial procedures, where liability, especially the doctors’, is being assessed. Defining the relationship between conventional and non-conventional medicine is the challenge, which answers will be sought to within the framework of the round table.